Methods for phenotypic evaluation of crustose lichens with emphasis on Teloschistaceae (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
We present methods for phenotype evaluation of crustose lichens, which enhances the chances to identify highly similar taxa using anatomical and morphological features. The basic idea is to evaluate characters with regard to completeness and reproducibility. We composed a list of about 100 basic characters and propose standardized ways of measuring them. We also present a list of morphological and anatomical terms with their standardized meaning. Basic guidelines for collecting, preparing and measuring lichen material are described. The proposed phenotypic evaluation process has two levels: (1) a pilot study is carried out on a restricted number of samples, but all available characters are evaluated; (2) a detailed study of a large number of samples that includes only potentially diagnostic features that are chosen from the pilot study according to their discriminatory weight.
Keywords: character evaluation, lichen anatomy, morphology, phenotype description, standardization.